2006
DOI: 10.1038/sj.onc.1209364
|View full text |Cite
|
Sign up to set email alerts
|

MKP1/CL100 controls tumor growth and sensitivity to cisplatin in non-small-cell lung cancer

Abstract: Non-small-cell lung cancer (NSCLC) represents the most frequent and therapy-refractive sub-class of lung cancer. Improving apoptosis induction in NSCLC represents a logical way forward in treating this tumor. Cisplatin, a commonly used therapeutic agent in NSCLC, induces activation of N-terminal-c-Jun kinase (JNK) that, in turn, mediates induction of apoptosis. In analysing surgical tissue samples of NSCLC, we found that expression of MKP1/CL100, a negative regulator of JNK, showed a strong nuclear staining fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
99
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 31 publications
8
99
0
Order By: Relevance
“…NSCLC cells expressing a smallinterfering RNA (siRNA) specific for DUSP1 were more sensitive to cisplatin and grew more slowly when injected into nude mice. Chemical compounds that inhibit DUSP1 expression also induce higher sensitivity to cisplatin (Chattopadhyay et al, 2006). These results suggested that DUSP1 is an important target for tumor regression and understanding its function might lead to improvements in cell-death promoting chemotherapy.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…NSCLC cells expressing a smallinterfering RNA (siRNA) specific for DUSP1 were more sensitive to cisplatin and grew more slowly when injected into nude mice. Chemical compounds that inhibit DUSP1 expression also induce higher sensitivity to cisplatin (Chattopadhyay et al, 2006). These results suggested that DUSP1 is an important target for tumor regression and understanding its function might lead to improvements in cell-death promoting chemotherapy.…”
mentioning
confidence: 82%
“…Identification of genes differentially expressed in parental control versus DUSP1-deficient H460 lung cancer cells We have previously reported that expressing DUSP1-siRNA in H460 cells (H460cri) (Chattopadhyay et al, 2006) resulted in earlier phosphorylation of JNK and p38 in response to CDDP and differences in tumor growth. Thus, changes in gene expression controlled by both kinases could underlie this observation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the physiological significance of unphosphorylated STAT6, the sensitivity of apoptosis of the STAT6 DN cells and STAT6Y641W cells was investigated. Cisplatin, a commonly used chemotherapeutic reagent in lung cancer treatment (Wang and Lippard, 2005;Chattopadhyay et al, 2006), was utilized to treat the cells. The induction of apoptosis was determined by poly ADP-ribose polymerase (PARP) cleavage through Western analysis.…”
Section: Unphosphorylated Stat6 Affects Cell Sensitivity To Apoptosismentioning
confidence: 99%
“…17 To test the significance of hrEPO supplementation with regard to tumor growth, aliquots containing 5 x 10 3 cells were seeded on a 24-well plate in standard medium supplemented either with 0.5% or 10% FBS ± 8 IU hrEPO. At subsequent 24 hourly intervals, cells were fixed with 1% glutaraldehyde and the number of cells determined by staining with crystal violet.…”
Section: Methodsmentioning
confidence: 99%